PENDIDIKAN KARAKTER PRESPEKTIF AL QUR’AN DAN HADITS - Yusuf Arifin; Sriyono Fauzi (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2026)
This study aims to examine in depth the concept of character education from the perspective of the Qur’an and Hadith as the authoritative sources of Islamic teachings. Using a qualitative-descriptive approach and thematic analysis method (tafsir maudlu’i), this research identifies the character dimensions constructed by these two primary sources. The findings reveal that the Qur’an lays the philosophical foundation of character education through four main dimensions: the theological dimension (tawhid), the social-familial dimension (birrul walidain), the personal integrity dimension (enjoining good and forbidding evil), and the interpersonal dimension (adab and communicative ethics). Meanwhile, the Prophetic Hadith serves as a concrete operationalization model encompassing the values of truthfulness (sidq), trustworthiness (amanah), compassion (rahmah), and justice (’adl). The integration of both sources yields a holistic character education paradigm, balancing the vertical dimension (hablum minallah) and the horizontal dimension (hablum minannas). The relevance of this paradigm in the modern era is manifested through the methods of exemplary conduct (uswah hasanah), habituation, and moral vigilance (muraqabah), which are capable of addressing the challenges of moral degradation in digital society.